Effect of energy expenditure on pregnancy outcome; A cohort study - C Abeysena; P Jayawardana; R De A Seneviratne (College of Community Physicians of Sri Lanka, 2011)
Objective: To determine the trimester specific effect of energy expenditure on pregnancy outcome. Study Design: A population based prospective cohort study was carried out in two Medical Officer of Health areas in the Gampaha District from May 2001 to April 2002. Eight hundred and seventy five pregnant women were recruited on or before 16 weeks of gestation. Daily energy expenditure was assessed based on the activities re-sorted at home by housewives and both at home and at work by working mothers indicated in the three day activity record on two occasions during second (n=371) and third (n=271) trimesters. Information on potential confounding factors was gathered on average at 12th 28th and 36th weeks of gestation. There were no statistically significant difference between responders and non-responders in terms of socio-economic characteris-tics. Multiple logistic regression was applied and the results are expressed as odds ratios (OR) and 95% confidence intervals (95%CI). Results: Energy expenditure >2550 kcal/day during second trimester was a risk factor for maternal complications [OR 6.30; 95%CI: 1.8, 21.9]. During third trimester it was a protective factor [OR 0.29; 95%CI: 0.09, 0.96] for small for gestational age defined as <5 centile. Energy expenditure had no association with low birth weight or preterm birth either in second or third trimesters. Conclusion: High energy expenditure was a risk factor for maternal complications and a protective factor against the birth of a small for gestational age infant in uncomplicated pregnancies. Key words: Birth weight; energy expenditure; preeclampsia; preterm birth; small for gestational age DOI: 10.4038/jccpsl.v13i2.2962 Journal of the College of Community Physicians of Sri Lanka Vol.13(2) 2008 1-8